Padronização da extração de DNA em tecidos de camundongos fixados em formalina e embebidos em parafina (FFPE) infectados experimentalmente com Angiostrongylus costaricensis - Alves, Bárbara Rodrigues (2013)
Abdominal angiostrongyliasis is a zoonotic infection caused by Angiostrongylus costaricensis, a nematode with intravascular location in the mesentery. Humans become accidentally infected by ingesting food or water contaminated with third stage larvae present in mucus secreted by intermediate hosts, terrestrial mollusks. The confirmed diagnosis of human infection is made only through histopathology of biopsies or mesenteric tissues removed during surgical treatment. There are many cases in which the pathology is very suggestive however there is no evidence of parasite structures in the sections. Thus, the goal of this study was to standardize the extraction of DNA from formalin fixed paraffin embedded (FFPE) tissues from mice experimentally infected with Angiostrongylus costaricensis for DNA detection and future study of human angiostrongyliasis suspected cases. Materials and methods: 45 samples of each tissue of liver, lung, intestine and mesentery, totalizing 180 samples from 15 infected mice with A.costaricensis. Worms of Angiostrongylus cantonensis were separately embedded in paraffin as controls. From embedded tissues, histological sections of 3 μm were performed and stained with HE to confirm the presence of parasite structures under the microscope. Approximately 24 to 31 sections of 10 μm were used for DNA extraction. Worms were embedded in paraffin under different conditions such as fixative chemicals, time of fixation and types of paraffin. Specific DNA of Angiostrongylus was detected by Polymerase Chain Reaction (PCR) to amplify a sequence of 232bp, previously designed for detection in human serum assays. There was a positive amplification in 33 samples from liver, 12 from lung, 45 from mesentery and 36 from intestine wall. For different conditions of embedment, the amplification of the DNA with the buffered formalin fixative was more efficient compared to the unbuffered one; the time of fixation and the commercial brand of wax did not affect the detection of nucleic acids, however, the ratio of paraffin to tissue appears to influence the performance of the method since samples with residual paraffin no amplification was obtained. The 232bp segment also was not visualized in samples where there was no evidence of presence of parasite structures, suggesting that histopathology findings should guide the choice of the samples for DNA extraction, and those most likely to have parasite structures surrounding the lesion, even if degraded. The description of the performance of PCR in paraffin embedded tissues as a diagnostic tool in human abdominal angiostrongyliasis depends on the detailed evaluation criteria in histopathology and their association with a positive amplification of the specific probe.